Group work Theories and Practices - Siddiqui, H.Y. (Jaipur, 2008)
Group Work: Theories and Practices is the first text on the subject written by an Indian author. Group work method is widely used in the subcontinent, particularly in India, Pakistan, Bangladesh and Sri Lanka. It has emerged as a vital strategy for empowering women, and helping children, youth and the elderly in a variety of settings. The text offers an insight into theories and assumptions thrown up by social science research globally. It also suggests guidelines for using them, keeping in mind the practice realities in developing countries such as India. The students and educators of social work, adult education, rural and child development, and scores of workers and professionals working with groups, would find it helpful in accomplishing their objectives.
Keywords: Groups-Research